Dynamics of RecA-mediated repair of replication-dependent DNA breaks - Amarh, Vincent (J Cell Biol, 2018)
Chromosomal replication is the major source of spontaneous DNA double-strand breaks (DSBs) in living cells. Repair of these DSBs is essential for cell viability, and accuracy of repair is critical to avoid chromosomal rearrangements. Repair of replication-dependent DSBs occurs primarily by homologous recombination with a sister chromosome. However, this reaction has never been visualized at a defined chromosomal locus, so little is known about its spatial or temporal dynamics. Repair of a replication-independent DSB generated in Escherichia coli by a rare-cutting endonuclease leads to the formation of a bundle of RecA filaments. In this study, we show that in contrast, repair of a replication-dependent DSB involves a transient RecA focus localized in the central region of the cell in which the DNA is replicated. The recombining loci remain centrally located with restricted movement before segregating with little extension to the period of postreplicative sister-chromosome cohesion. The spatial and temporal efficiency of this reaction is remarkable.